PENGARUH MODAL KERJA, BIAYA PRODUKSI DAN PENJUALAN TERHADAP LABA BERSIH PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA TAHUN 2019-2022 - Ilham Aditya Septariyadi; Anzu Elvia Zahara; Khairiyani (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to determine the effect of working capital, production costs and sales on net income of mining companies listed on the Indonesian Sharia Stock Index for 2019-2022. This study uses independent variables, namely working capital, production costs and sales. With the dependent variable is net income. The data used in this study is secondary data, namely in the form of financial reports of food and beverage manufacturing companies registered at ISSI for 2019-2022. This research is a descriptive research with a quantitative approach. Statistical methods using multiple linear regression analysis, t test, f test, and analysis of the coefficient of determination. The results of this study indicate that working capital and sales variables affect net income. Meanwhile, the production cost variable has no effect on net income. By using the F test it is found that the independent variables have a simultaneous influence on the dependent variable. From the determination calculation, the Adjusted R Square value is 0.213 or 21.3%. This means that it indicates that the variables of working capital, production costs and sales on net income have an effect of 21.3% and the remaining 78.7% can be influenced by other factors outside of this study.